Visual metaphor of sadness in poetry comics: a socio-cognitive perspective - Suijun Wen; Zenan Zhong; Shukun Chen (Frontiers in Psychology, 2023)
Earlier literature on conceptual metaphor studies has extensively examined verbal metaphors of sadness in different text types and with cultural variations. However, there has been by far limited research on the visual metaphor of sadness. Adopting a socio-cognitive perspective, this study investigates the conceptual metaphor of sadness in the exemplary case of Chinese poetry comics drawn by Cai Zhizhong. The findings reveal that (1) BEING SAD IS BEING CONFRONTED WITH NATURAL FORCE and BEING SAD IS BEING PHYSICALLY ISOLATED are the two most frequently occurring visual metaphors across the panels; (2) all the visual metaphors at play can be explained according to the conceptual metaphor theory; (3) SADNESS IS BITTERSWEET FOOD OR DRINK and BEING SAD IS BEING PHYSICALLY ISOLATED are two additional kinds of sadness metaphors identified; and (4) the visual metaphors of sadness with Chinese cultural variations are rooted in mainstream Chinese cultural philosophies in the relevant period of history. The article also discusses the underlying mechanisms of the investigated visual metaphors in the Chinese culture by unveiling three cultural characteristics in the particular context.